Analysis of Feedback Parameter with Vibration Sensor on Signal Self-Mixing Interferometry - Novi D. Ariyanti; Endarko Endarko; Agus Rubiyanto (IPTEK Journal of Proceedings Series, 2019)
In the research aims to analyzed feedback parameter on Self-Mixing Interferometry (SMI) signals. It is because the feedback parameter is one of the determined parameters in SMI vibration sensor research. The experimental apparatus consists of a laser diode as the light source, mirror as a target, collimator as light alignment, and PLX-DAQ as data acquisition executed by Arduino Uno. The principle of data retrieval with the manner of the light source is directed exactly perpendicular to the vibrating target, then reflected and arrested by the detector (photodiode) contained in the laser diode. Light arrested by the photodiode in the form of optical value then automatically converted into voltage value displayed on a personal computer (PC). This feedback on SMI is obtained by variation of the vibration frequency given to a target. The variation of vibration given is 10-100 Hz with 10 Hz increment and each frequency is taken 1000 data. Based on the research that has been done then results obtained at the frequency of 10-30 Hz feedback does not appear because the vibration small so that the vibration sensor is less than optimal. Feedbacks appear at frequencies 40 Hz and 50 Hz but are clearly visible at frequencies 50 Hz. While at 60-80 Hz frequency feedback begins to disappear. The existence of feedback on frequency 50 Hz indicated that vibration sensors on SMI can be applied to industry and medical field